2011
DOI: 10.1002/pon.1946
|View full text |Cite
|
Sign up to set email alerts
|

Screening for distress and supportive care needs during the initial phase of the care process: a qualitative description of a clinical pilot experiment in a French cancer center

Abstract: Objective: To provide a qualitative description of a clinical pilot experiment in a French cancer center, conducted by a nurse after the treatment decision consultation attended by new cancer patients during the initial phase of the care process.Methods: The Psychological Distress Thermometer (PDS) and a problem checklist were administered to 255 patients before nurse consultation, helping her to manage the clinical interview, explore patient's distress and supportive care needs, and finally refer the patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 42 publications
3
40
0
Order By: Relevance
“…A further key issue is to respond to barriers surrounding the discussion of psychosocial distress, which were prominent in these data. Furthering others' suggestion (Carlson et al, 2012;Dolbeault et al, 2011;National Institute for Clinical Excellence, 2014) these data indicate that further training is likely to be crucial towards addressing clinicians' low confidence and enabling them to deliver the psychosocial needs assessments effectively. Patients' understandings of the radiographer/ chemotherapy nurse remit should also be tackled.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…A further key issue is to respond to barriers surrounding the discussion of psychosocial distress, which were prominent in these data. Furthering others' suggestion (Carlson et al, 2012;Dolbeault et al, 2011;National Institute for Clinical Excellence, 2014) these data indicate that further training is likely to be crucial towards addressing clinicians' low confidence and enabling them to deliver the psychosocial needs assessments effectively. Patients' understandings of the radiographer/ chemotherapy nurse remit should also be tackled.…”
Section: Discussionmentioning
confidence: 79%
“…Training is also pinpointed as important where non-specialist professionals are involved in distress screening and needs assessment (Carlson et al, 2012;Dolbeault et al, 2011). Further understanding of such issues is essential to ensure interventions aiming to reduce distress benefit patients.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, one radiotherapist did not discuss the SIPP with the patients at all during consultation . In addition, in line with the study of Dolbeault and colleagues , there was a certain amount of (initial) resistance because two of the seven radiotherapists did not recognise the value of psychosocial screening . The fourth limitation is that we collected no data about the content of psychosocial support received and/or whether the support was sufficient to cope with the psychosocial and medical aspects of the cancer.…”
Section: Discussionmentioning
confidence: 82%
“…Some studies found that patients who reported a higher burden of emotional symptoms were more likely to access services than those who reported a lower burden of symptoms [1216]. Referral rates and resource utilization still seem low, given documented high levels of distress.…”
Section: Introductionmentioning
confidence: 99%